2021
DOI: 10.3389/fpsyg.2021.695288
|View full text |Cite
|
Sign up to set email alerts
|

A Cluster Randomized Trial of Promoting Alternative Thinking Strategies (PATHS®) With Swedish Preschool Children

Abstract: The preschool edition of Promoting Alternative THinking Strategies (PATHS®) is a school-based, teacher implemented universal intervention developed in the United States designed to promote social emotional competence (SEC) in children as a foundation for improved mental health. PATHS is delivered as a curriculum and it is based on theories and research regarding SEC, brain development, and optimal school environments. A majority of children in Sweden attend preschool, which is government-subsidized and follows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…The protocol was registered at ClinicalTrials.gov (NCT04512157) after the trial was completed. As noted, the overview of the PATHS program including details concerning the topics and dosage, as well as the results of the main outcome evaluation for this trial of PATHS and moderation analyses by gender has been reported elsewhere (Eninger et al, 2021;Ferrer-Wreder et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The protocol was registered at ClinicalTrials.gov (NCT04512157) after the trial was completed. As noted, the overview of the PATHS program including details concerning the topics and dosage, as well as the results of the main outcome evaluation for this trial of PATHS and moderation analyses by gender has been reported elsewhere (Eninger et al, 2021;Ferrer-Wreder et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Table 3 shows the standardized interaction parameter estimates from the tested SEM models, and Table 4 shows the observed subgroup mean and standard deviations. The cut off for the interpretation of a substantive difference between subgroups was set as: (1) a standardized parameter estimate of an absolute value of ±0.20 or higher based on the benchmarks developed earlier intervention studies (e.g., Taylor et al, 2017;Eninger et al, 2021) and ( 2) the interaction effect should be within the range of the confidence intervals. Using this criterion and analysis approach, we found three interaction effects between PATHS (intervention/control) and preschool neighborhood income (advantaged/disadvantaged) with significant differences between the subgroups.…”
Section: H2: Intervention Moderation Analysismentioning
confidence: 99%
See 3 more Smart Citations